Material Matters: Unraveling the effect of biodegradable plastic polyhydroxybutyrate (PHB), conventional high-density polyethylene (HDPE), and bamboo on the bacterial community of marine eulittoral sediments - Aniruddha Bhalerao; Urda Dueker; Miriam Weber; Andreas Eich; Christian Lott; Jacek Lecinski; Hans Josef Endres; Regina Nogueira (Heliyon, 2025)
Plastics pose a significant environmental threat, prompting extensive studies on their impact. These studies often focus on the differential bacterial compositions of biofilms growing on plastic surfaces. However, little is known about the influence of plastics on bacterial communities in surrounding environments such as eulittoral sandy beach sediments. Therefore, we investigated the effects of high-density polyethylene (HDPE) and biodegradable plastic alternative, polyhydroxybutyrate (PHB), alongside bamboo as a natural material, on Mediterranean Sea beach sediments in a 258-day field test. After exposure, 16S rDNA sequencing analysis revealed that a distinct bacterial community developed in the sediments surrounding test materials, differing significantly from natural sediments that were not in contact with test materials. The test material-contact sediment displayed a higher relative abundance of bacterial orders capable of test material biodegradation. The test material's impact on surrounding sediments varied depending on its type and biodegradability. The sediments in contact with biodegradable materials (PHB and Bamboo) showed a higher number of unique orders than HDPE-contact and natural sediments. The comparison of biofilm growing on PHB with PHB-contact and natural sediments showed that the PHB biofilm contained a higher abundance of PHB-degrading bacterial orders (e.g. Desulfobacterales) and its bacterial composition was significantly different from that of PHB-contact and natural sediments, indicating that the effect of the test materials was most pronounced on their surface. Our study is novel as it demonstrates that the effects of plastics, their replacements, and natural materials extend beyond surface biofilms and impact surrounding environments, emphasizing the need for future research to consider the broader ecological implications of plastics.